2008
DOI: 10.1152/ajpgi.90322.2008
|View full text |Cite
|
Sign up to set email alerts
|

Electroacupuncture improves impaired gastric motility and slow waves induced by rectal distension in dogs

Abstract: puncture improves impaired gastric motility and slow waves induced by rectal distension in dogs. Am J Physiol Gastrointest Liver Physiol 295: G614 -G620, 2008. First published July 24, 2008 doi:10.1152/ajpgi.90322.2008 is known to induce upper gastrointestinal (GI) symptoms. The aim of this study was to investigate the effects and underlying mechanisms of RD on gastric slow waves (GSW) and motor activity and furthermore to investigate the effects and mechanisms of electroacupuncture (EA) on GSW and motor acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
112
1
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 88 publications
(121 citation statements)
references
References 46 publications
(59 reference statements)
6
112
1
2
Order By: Relevance
“…Fleet Lynchburg, VA, USA), a rectal catheter with a balloon attached to its tip (the caudal pole of the balloon was about 6 cm from the anal verge) was inserted into the rectum and affixed before a test meal for gastric emptying. The balloon was inflated with 120 ml of air (7,21) only during 60 -90 min after the test meal that was identical to the meal in experiment 1. In the control session, no catheter was inserted into the rectum and no RD or EA or sham-EA was performed.…”
Section: Experimental Protocolsmentioning
confidence: 99%
See 3 more Smart Citations
“…Fleet Lynchburg, VA, USA), a rectal catheter with a balloon attached to its tip (the caudal pole of the balloon was about 6 cm from the anal verge) was inserted into the rectum and affixed before a test meal for gastric emptying. The balloon was inflated with 120 ml of air (7,21) only during 60 -90 min after the test meal that was identical to the meal in experiment 1. In the control session, no catheter was inserted into the rectum and no RD or EA or sham-EA was performed.…”
Section: Experimental Protocolsmentioning
confidence: 99%
“…Previous studies have reported that EA at ST36 accelerated gastric emptying in both dogs and humans (34,49) and restored impaired gastric accommodation in vagotomized dogs (33). A recent study reported that EA improved RD-induced impairment of antral contractions (7). Mechanistically, a number of previous studies have shown the involvement of the opioid pathway with the prokinetic effect of EA on gastrointestinal contractions (7,42).…”
mentioning
confidence: 95%
See 2 more Smart Citations
“…EA at ST36 restored rectal distentioninduced impairment in gastric slow waves in dogs and increased the spikes in rabbits. [35][36][37] EA at ST36 improved the percentage of normal gastric slow waves as well as the percentage of tachygastria in healthy volunteers. 38 Liu et al 21 reported that 2-week TEA at ST36 decreased dyspepsia symptoms and elevated vagal activity in patients with functional dyspepsia.…”
Section: Discussionmentioning
confidence: 90%